KRÓTKI ZARYS EWOLUCJI FILOLOGII: UJĘCIE ‘PORTALOWE’ - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2019)
In the paper, the author postulates that philology may be characterized by an evolutionary sequence: from classical philology, to modern native and nonnative types of philologies, to the expected panphilology. The portals perspective applied in the paper has allowed the author to investigate all four evolutionary phases with special emphasis on the latest phase of the proposed evolutionary sequence. Panphilology has been described in greater detail as characterized by such features as an open and eclectic type of studies, cosmopolitanism and students' freedom in selecting their highly individual paths of studies.